The genus Heterotarsus Latreille (Coleoptera: Tenebrionidae: Opatrini) in India - T.k., Viswanath; Hegde, Vishwanath D.; K.m., Remia (Zootaxa, 2026)
The study of the genus Heterotarsus from India, resulted in the discovery of the Sri Lankan species Heterotarsus ceylonicus Kaszab, 1976 from India. In addition to the identification key, images of type specimens and examined material, diagnosis and checklist of Heterotarsus species from India are provided.